Athletes movement tracking device for soccer players - Archevapanich, Tuanjai; Sithiyopasakul, Jirayus; Sithiyopasakul, Jiran; Sithiyopasakul, Paisan; Anuwongpinit, Thanavit; Purahong, Boonchana (My University, 2021)
This article presents the design and development of real-time tracking system using GPS for soccer players. The tracking system is separated into two parts including hardware and software sections. The hardware uses NodeMCUV3 which is connected to the GPS module that can receive a current position data of soccer players. After that, it processes and records the position data into the MicroSD card module. In the software section can display the heat map results from recorded data of soccer players. The main user is a soccer club manager which is responsible for monitoring the data that tested on the movement of the soccer player. For the experimental results, a device is tested, and the movement data is collected. Also, it is found that the tracking device could track the athlete's movements successfully.
Keywords: Athletes; Data; Devices; Soccer